Membangun perekonomian desa berkelanjutan melalui manajemen kinerja berbasis community empowerment - Alif Muhammad Zakaria; Mauliyana Rachmat (Oetoesan-Hindia: Telaah Pemikiran Kebangsaan, 2021)
ABSTRACT : The village is the basic social basis of a country's order, therefore empowering rural communities is very important to support a sustainable economy, performance management through empowerment is the main key in overcoming human resource problems such as poverty, unemployment and social inequality. This study uses qualitative analysis methods, the research data was obtained from literature and field studies in Samirono Getasan Village, Semarang Regency by looking for competent sources, sources of government and private institutions that support and are relevant. Data analysis was performed with a descriptive approach that outlined the facts along with the data obtained at the study site. The results of this study prove that performance management based on community potential empowerment has a significant role in building a sustainable rural economy.